Firm wage premia, industrial relations, and rent sharing in Germany - Hirsch, Boris; Müller, Steffen (Munich, 2018)
"This paper investigates the influence of industrial relations on firm wage premia in Germany. OLS regressions for the firm effects from a two-way fixed effects decomposition of workers’ wages by Card, Heining, and Kline (2013) document that average premia are larger in firms bound by collective agreements and in firms with a works council, holding constant firm performance. RIF regressions show that premia are less dispersed among covered firms but more dispersed among firms with a works council. Hence, deunionization is the only among the suspects investigated that contributes to explaining the marked rise in the premia dispersion over time."